ASSESSMENT OF IMPACT WAVE MOVEMENT THROUGH NONSTANDARD CONTRA-FORCES IN THE MAXILLOFACIAL REGION POST ELECTRIC SCOOTER ACCIDENTS - Boymuradov Shukhrat Abdujalilovich; Khatamov Ulugbek Altibayevich; Shakirov Akmal; Shokirova Farangiz Shavkatovna (Scholar Express Journals, 2025)
The use of personal mobility devices, particularly electric scooters, is rapidly increasing, which is accompanied by a rise in injuries, including those in the maxillofacial region. Studying the propagation of shock waves through unusual contra-forces in this area following electric scooter accidents can provide a deeper understanding of injury mechanisms and contribute to the development of effective prevention and treatment methods.
Keywords: Road traffic accident; personal mobility devices; fractures